Effects of skim milk and isotonic drink consumption before exercise on fluid homeostasis and time-trial performance in cyclists: a randomized cross-over study - Danniela García-Berger; Karen Mackay; Matias Monsalves-Alvarez; Carlos Jorquera; Rodrigo Ramirez-Campillo; Hermann Zbinden-Foncea; Mauricio Castro-Sepulveda (Taylor & Francis Group, 2020)
Background Hydration status affects endurance performance. Pre-exercise hydration recommendations target the consumption of high carbohydrate and sodium beverages. Milk, due to its carbohydrate and sodium content, may be considered an effective pre-exercise hydration beverage. Purpose In a randomized cross-over trial, we compared the effects of an isotonic sport drink (SPD) with skim milk (SM) consumption before a race, on fluid homeostasis and time-trial performance in road cyclists. Methods Male road cyclists (n = 9; age, 26.8 ± 4.78 years) with 10.8 ± 8.56 years of experience in national competitions, consumed either SPD or SM in doses of 350 mL at 3 h and 350 mL at 1.5 h before a 18.6 km time-trial race. Measurements of body mass, urine specific gravity (USG), urine color and time-trial were compared between drinks (group; g) before and after the race (time; t). Results The two-way ANOVA showed no differences between SPD and SM in body mass (t, p < 0.0001; g, p = 0.89; t × g, p = 0.54), USG (t, p = 0.01; g, p = 0.63; t × g, p = 0.29) and urine color (t, p = 0.01; g, p = 0.54; t × g, p = 0.28) before or after race. Furthermore, no differences on water consumption during the race (p = 0.55) or time-trial performance (p = 0.84) were observed between trials. Conclusion Current results may help athletes with different beverages preferences to increase their options of hydration strategies.